Advancement in biomedical implant materials—a mini review - S., Ashish Daniel; P., Suya Prem Anand; Naveen, Jesuarockiam; Khan, Tabrej; Khahro, Shabir Hussain (Frontiers in Bioengineering and Biotechnology, 2024)
Metal alloys like stainless steel, titanium, and cobalt-chromium alloys are preferable for bio-implants due to their exceptional strength, tribological properties, and biocompatibility. However, long-term implantation of metal alloys can lead to inflammation, swelling, and itching because of ion leaching. To address this issue, polymers are increasingly being utilized in orthopedic applications, replacing metallic components such as bone fixation plates, screws, and scaffolds, as well as minimizing metalon-metal contact in total hip and knee joint replacements. Ceramics, known for their hardness, thermal barrier, wear, and corrosion resistance, find extensive application in electrochemical, fuel, and biomedical industries. This review delves into a variety of biocompatible materials engineered to seamlessly integrate with the body, reducing adverse reactions like inflammation, toxicity, or immune responses. Additionally, this review examines the potential of various biomaterials including metals, polymers, and ceramics for implant applications. While metallic biomaterials remain indispensable, polymers and ceramics show promise as alternative options. However, surfacemodified metallic materials offer a hybrid effect, combining the strengths of different constituents. The future of biomedical implant materials lies in advanced fabrication techniques and personalized designs, facilitating tailored solutions for complex medical needs